2018
DOI: 10.1007/s00784-018-2367-4
|View full text |Cite
|
Sign up to set email alerts
|

Oral health-related quality of life changes in children following dental treatment under general anaesthesia: a meta-analysis

Abstract: Dental treatment under GA significantly improved the OHRQoL of children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 55 publications
1
23
0
1
Order By: Relevance
“…A recent meta‐analysis indicated that DGA significantly improved the OHRQoL of children . The present study, however, only evaluated the FIS changes.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…A recent meta‐analysis indicated that DGA significantly improved the OHRQoL of children . The present study, however, only evaluated the FIS changes.…”
Section: Discussionmentioning
confidence: 94%
“…49 A recent meta-analysis indicated that DGA significantly improved the OHRQoL of children. 10 The present study, however, only evaluated the FIS changes. Heterogeneity can potentially reduce the strength of the overall results; however, in the present meta-analysis measures were undertaken to ensure the integrity of the results.…”
Section: Studiesmentioning
confidence: 94%
See 1 more Smart Citation
“…OHQoL measures need to be sensitive to treatment (ie produce a significant change in scores following treatment/intervention) and ideally an ability to identify changes in OHQoL in relation to clinical importance (responsiveness). A systematic review and meta‐analysis have identified improvements in OHQoL following dental treatment under general anaesthesia in children in all studies, and an overall “large” magnitude of improvement, at least in the short term . Given the advances in the field and the availability of standardized OHQoL measures, incorporating OHQoL assessments should be encouraged to provide greater understanding of the consequences of ECC locally and globally so as to prioritize need.…”
Section: Impact Of Ecc On Oral Health‐related Quality Of Lifementioning
confidence: 99%
“…A systematic review and meta-analysis have identified improvements in OHQoL following dental treatment under general anaesthesia in children in all studies, and an overall "large" magnitude of improvement, at least in the short term. 31 Given the advances in the field and the availability of standardized OHQoL measures, incorporating OHQoL assessments should be encouraged to provide greater understanding of the consequences of ECC locally and globally so as to prioritize need. Moreover, there is a need to provide further evidence of the benefits of managing ECC to children's lives, their families, and their communities, including the benefits of preventive care.…”
Section: Health-related Qualit Y Of Lifementioning
confidence: 99%